2010
DOI: 10.1177/104063871002200412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salmonella Serovar Isolation and Antimicrobial Resistance Patterns from Porcine Samples Between 2003 and 2008

Abstract: Abstract. Food-borne Salmonella infections can produce symptoms from mild gastroenteritis to severe systemic disease and death, representing an important public health issue in U.S. livestock and livestock products, which have been implicated as frequent sources of Salmonella contamination. Concerns have been raised about the spread of antibiotic resistance in Salmonella strains, particularly those that originate from food animal sources, as a result of prophylactic and therapeutic antimicrobial use in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A reason for these differences might be varying antimicrobial usage regimes in pig production ( [Ling et al, 2001], [Valdezate et al, 2005], [Zhao et al, 2007], and [Xia et al, 2009]). An increased antimicrobial resistance to sulfadimethoxine and spectinomycin has been also reported in S. Derby isolated from U.S. livestock between 2003 and 2008 (Clothier et al, 2010). Genotyping of antimicrobial resistance genes in strains from Southern Brazil and America ( [Michael et al, 2006], [Zhao et al, 2007] and [Anjum et al, 2011]) revealed sul1, sul2, aadA2, tet(A), tet(B), bla TEM and dfrA14.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A reason for these differences might be varying antimicrobial usage regimes in pig production ( [Ling et al, 2001], [Valdezate et al, 2005], [Zhao et al, 2007], and [Xia et al, 2009]). An increased antimicrobial resistance to sulfadimethoxine and spectinomycin has been also reported in S. Derby isolated from U.S. livestock between 2003 and 2008 (Clothier et al, 2010). Genotyping of antimicrobial resistance genes in strains from Southern Brazil and America ( [Michael et al, 2006], [Zhao et al, 2007] and [Anjum et al, 2011]) revealed sul1, sul2, aadA2, tet(A), tet(B), bla TEM and dfrA14.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, some studies used pulsed-field gel electrophoresis to elucidate the spread of S. Derby in slaughterhouses (Giovannacci et al, 2001), or to investigate the genetic diversity of the serovar in France ( [Kerouanton et al, 2007] and [Kerouanton et al, 2010]), Spain (Valdezate et al, 2005), Hong Kong (Ling et al, 2001), China (Xia et al, 2009) or Brazil (Michael et al, 2006). Clinical, food and animal isolates showed a wide range of PFGE and antimicrobial resistance profiles, often either implicated streptomycin, tetracycline, or sulfonamides ( [Valdezate et al, 2005], [Michael et al, 2006], [Gebreyes et al, 2004] and [Clothier et al, 2010]). …”
Section: Introductionmentioning
confidence: 99%
“…(Table 3). The reason for targeting S. Choleraesuis in swine is due to its high carriage rate; it constituted 57.3% of isolates from swine in the United States in 2003 (54,55). Moreover, this serovar is documented as among the most invasive Salmonella serovars.…”
Section: Vaccines Against Serogroup C Ntsmentioning
confidence: 99%
“…This explains the reason why the susceptibilities of all strains to antibiotics were not increased in the presence of CCCP and PAbN [20]. Furthermore, the intrinsic resistance of WT-ST, CI-ST, and CA-ST to antibiotics could cause the decrease in susceptibility regardless of efflux pump activity [21].…”
Section: Resultsmentioning
confidence: 97%